Програмна система для проведення опитувань та аналізу їх результатів - Мічурін, І. Є. (ХНУРЕ, 2022)
Today, there are many paper and electronic survey systems used by psychologists, sociologists, politicians, employers, and educators to obtain information about workers, their attitudes toward work, their emotional state, and so on. There is a need to improve the accuracy of the information obtained and its conclusions, not by increasing the number of questions, but by improving the analysis of the data obtained. There is also a tendency to identify hidden patterns through a system of indirect questions.